A new neutronics-thermal-mechanics multi-physics coupling method for heat pipe cooled reactor based on RMC and OpenFOAM. (September 2021) - Guo, Yuchuan; Li, Zeguang; Huang, Shanfang; Liu, Minyun; Wang, Kan
Abstract: Based on the characteristics of heat pipe cooled reactors, this study presents a new multi-physics coupling method by employing the Monte Carlo transport code RMC and the open-source code OpenFOAM. Three typical physical processes are considered, i.e., the neutron transport, the heat conduction and the thermal expansion. To conduct the steady-state coupling calculation, an investigation is conducted on the thermal deformation simulation, the expansion reactivity feedback, the mesh mapping and the coupling method between two codes. By employing this method, the coupling calculation on a typical heat pipe cooled reactor named KRUSTY (Kilowatt Reactor Using Stirling TechnologY) is conducted. Compared with the existing results, the correctness of this method is verified. As indicated from the calculation, the reactivity feedback attributed to thermal expansion is dominant, which is nearly 90% of total reactivity feedback. Specific to fuel deformation, the thermal expansion primarily takes place on the "upper" and "lower" surfaces. As impacted by the high thermal conductivity of fuel, the total temperature difference in the reactor core is sufficiently small, which only reaches about 26K. The results and comparisons reveal the availability and feasibility of this coupling method, and such a method can effectively analyze heat pipe cooled reactors. Graphical abstract: The coupling calculation on KRUSTY protype reactor using the new neutronics-thermal-mechanics coupling method based on RMC and OpenFOAM. Image 1 Highlights: A Multi-physics Coupling Method for Heat Pipe Cooled Reactor is proposed. A solver is established to simulate the heat conduction and thermal expansion. The importance of expansion reactivity feedback is discussed.